The Perception of the Visiting Academics on Contact Sessions in an ODL System - Karunanayake, S.; Nawarathne, N.M.R.K. (University of Jaffna, 2012)
: This study investigated the perception of the visiting academics on contact sessions in an Open and Distance Learning (ODL) system. Questionnaires and interviews were used to collect information from the twenty-five visiting academics who are conducting contact sessions in Sinhala medium of the Post Graduate Diploma in Education Programme (PGDE) during the academic year 2010/2011. Findings indicated that all academics were aware of how to conduct contact sessions in an ODL system. The orientation workshops on contact sessions have helped visiting academics to update their knowledge on how to conduct contact sessions in an interactive manner in an ODL system. Further the visiting academics expect the department to organize a series of workshops to orient them to conduct contact sessions by using new technology to enhance their abilities in this regard. All visiting academics were satisfied with the information provided by the department on how to conduct contact sessions. But majority of the visiting academics were dissatisfied with the student prior preparation when attending the contact sessions. Some external academics were not satisfied with the facilities provided in the centres, such as library facilities, multimedia to enhance their teaching and learning process. Majority of the visiting academics have stated that the number of contact sessions for each subject should be increased. In order to improve the quality of contact sessions in line with ODL approach the number of suggestions were made by the external academics to incorporate in the PGDE programme.
Keywords: Contact Sessions; Open and Distance Learning (ODL); Visiting Academics